Anti-inflammatory effect of diethylcarbamazine citrate - Zhu Lan-qing; Liao Xi-lin; Feng Zheng-kang; Fan Cun-kun (Acta Pharmacologica Sinica, 2016)
Diethylcarbamazine citrate (DEC) at 180-300 mg/kg ip or 560 mg/kg ig inhibited hind paw swelling induced by sc 0.15 ml of carrageenan in normal and adrenalectomized rats. DEC ip 300 mg/kg also inhibited the same swelling induced by sc 2.5% formaldehyde in rats. The proliferation of granuloma induced by cotton-pellets tended to be inhibited by DEC, although not significantly. It inhibited the swelling of mouse ear induced by xylene and the increased vascular permeability induced by ip 0.7% HAC. DEC neither prolonged the survival time in adrenalectomized rats nor increased the weight of the adrenal or plasma cortisol levels in normal rats. DEC decreased the prostaglandin E content in inflammatory tissue, although less than the extent in the indomethacin group. These results indicate that the anti-inflammatory action of DEC is presumably due to the inhibition of synthesis or the release of prostaglandin E, in addition to a possible action mediated by its leukotriene synthesis inhibitor action.